A handbook of modern history world history since 1870 - Gibbons, S. R. (London Longman, 1986)
An alphabetically arranged handbook identifying events, features, and individuals of world history since 1870, from the Abdication Crisis to the Zulu War.
Includes index.
Keywords: History, Modern -- 19th century; History, Modern -- 20th century; History, Modern. -- 19th century; History, Modern. -- 20th century